Volatility integration of crude oil, gold, and interest rates on the exchange rate: DCC GARCH and BEKK GARCH applications - Shailesh Rastogi; Jagjeevan Kanoujiya; Adesh Doifode (Cogent Business & Management, 2024)
Literature is replete with evidence of market integration between crude oil, gold and interest rates (IR) with the exchange rate (ER) due to varied reasons. However, it is observed that the explored market integration is limited for the price and return volatilities. Bivariate GARCH models (BEKK-GARCH and DCC-GARCH) are used in this research to ascertain the conditional volatility association of gold, crude oil and yield (or IR) on the ER (the price of US in Indian rupee). The daily basis data from January, 2000 to December, 2022. Except for a few cases, it is found that the conditional covariance association of gold, crude oil and the yield on the ER are significant for both shocks and persistence. It confirms the economic theories of market connectivity. The results are as expected (from the previous literature) for conditional volatility, whereas findings regarding volatility spillover effects (VSE) and are surprising. The findings of the study imply the separation of price or returns integration from volatility integration. Co-movement of the prices has a limited impact; however, volatility integration has a larger and long-term impact. Therefore, the study endorses the views that gold, crude oil and IR markets can be treated separately from the ER markets with respect to the risk management of the ER. Studies involving volatility integration from these markets on the ER are not easily available. Therefore, there is a lack of knowledge about the nature of association with respect to the volatility among these markets, especially with respect to the ER market. The findings give key implication that government should consider these macroeconomic variables (gold-oil-interest) resilient against ER volatilities.
Keywords: 650; bivariate GARCH; crude oil; exchange rate; gold; interest rates; volatility